Islamic Law as the Authoritative Source in State Administration of Indonesia - Yayan Sopyan; Yazwardi; Ade Dedi Rohayana; Imam Yahya; Ismail (Jurnal Hikmatuna, 2022)
Many academicians are regretful about the removal of seven words in the Jakarta Charter and consider this as a political defeat for Muslims. If the words had not been removed, Islamic law would be simple in its implementation in Indonesia. There was a new hope when the Presidential Decree of 5 July 1959 stated to return to the 1945 Constitution. The Presidential Decree emphasized that the Jakarta Charter was a series of units in the Constitution. In other words, Islamic laws in the state administration system in Indonesia could be the authoritative source. This means that Islamic law has a chance to contribute to the Indonesian legal system. This qualitative research used normative approach in which the information was gained from a number of reliable sources such as books and journals to explore and figure out any perspectives about the status of Islamic law as the authoritative source in state administration of Indonesia. This research showed that Islamic law as the authoritative source is possible to contribute to legal order applied in Indonesia. As a political product, law relies on the political situation; nevertheless, the Muslims are not able to maximize their political roles given the hindrances from both external and internal factors. Hence, there is a need to build awareness of Muslims particularly those becoming the law makers to be capable of introducing the Islamic laws to public through the objectification of Islamic laws. Substantially, the Islamic law is more superior in giving justice, benefits and legal certainty.